Preliminary Report of Seroprevalence of Anti-Measles Immunoglobulin G among Healthcare Workers of 6 Teaching Hospitals of Daegu, Korea in 2019 - Chang, Hyun-Ha; Kim, Shin-Woo; Kwon, Ki Tae; Kim, Hye In; Kim, Min Jung; Ryu, Seong Yeol; Kim, Hyun Ah; Hur, Jian; Kwon, Hyun Hee; Hong, Hyo-Lim (Infection & chemotherapy, 2019)
The measles outbreak in Daegu of January 2019 made 6 teaching hospitals' organization test the measles immunity of their healthcare workers (HCWs). We found that 6,935 (75.9%) of 9,132 HCWs tested seropositive for anti-measles immunoglobulin G (IgG), and seropositivity rate was very different between 6 hospitals (range, 59.9-93.1%). The seroprevelence was lowest in the age of twenties, but the rate was different between 6 hospitals (range 47.0-85.5%). Therefore, to prevent measles from spreading to HCWs, each hospital should make their own data periodically about anti-measles IgG seropositivity of their HCWs.